Addition of Co3O4 to introduce pinning centre in Bi-Sr-Ca-Cu-O/Ag tapes - Awang Kechik, Mohd Mustafa; Mohd Aris, Mohd Faisal; Shaari, Abdul Halim; Chen, Soo Kien; Abd Shukor, Roslan (Universiti Putra Malaysia Press, 2008)
This study investigated the flux pinning capability of Co3O4 in Bi-Sr-Ca-Cu-O superconductor tapes. The Bi-Sr-Ca-Cu-O powders were prepared by using the co-precipitation technique with the addition of Co3O4 as pinning centre to enhance the transport critical current density (Jc) of the system. The Ag sheathed (Bi,Pb) 2Sr2Ca2Cu3O10 (2223) and (Bi,Pb) 2Sr2Ca2Cu3O10- ( Co3O4)0.01 high temperature superconductor tapes were fabricated using the powder in tube method. The effects of Co3O4 addition on the microstructure, critical temperature and critical current density were studied. The Jc value of the Co3O4 added tapes increased to ~4500 A/cm2. This tape showed the highest Jc and Tc when heated at 845°C for 50 hours. XRD diffraction pattern showed that the addition of Co3O4 inhibits the 2223 phase formation. This study shows that magnetic particles can act as effective pinning centres leading to the enhancement of Jc in the system.